Bisdemethoxycurcumin Inhibits Hepatocellular Carcinoma Proliferation Through Akt Inactivation via CYLD-Mediated Deubiquitination - Qiu C; Liu K; Zhang S; Gao S; Chen W; Li D; Huang Y (Dove Medical Press, 2020)
Chengjiang Qiu,1 Kairui Liu,1 Sheng Zhang,1 Simin Gao,2 Weirun Chen,1 Dateng Li,3 Youxing Huang1 1Department of Abdominal Surgery, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong Province, People’s Republic of China; 2Department of Breast Surgery, Breast Tumor Center, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Guangzhou, Guangdong Province, People’s Republic of China; 3Department of Statistical Science, Southern Methodist University, Dallas, TX 75275, USACorrespondence: Youxing HuangDepartment of Abdominal Surgery, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, No. 111 Dade Road, Guangzhou, Guangdong Province, People’s Republic of ChinaTel +86-13632255441Fax + 86-20-39318790Email waiqike7@163.comBackground: Bisdemethoxycurcumin (BDMC), a stable bioactive ingredient in curcuminoids, is associated with various antitumor functions, such as proliferation inhibition, metastasis suppression and apoptosis induction, in many cancer types. However, the mechanism of BDMC in hepatocellular carcinoma (HCC) remains unclear.Methods: We assessed the toxicity and the inhibitory effect of BDMC in the HepG2 cell line by using CCK-8 and colony formation assays. The regulatory effects of BDMC on Akt and MAPK signaling were investigated by Western blotting and immunoprecipitation.Results: We found that the half-maximum inhibitory concentration (IC50) of BDMC after 48 hrs of treatment was 59.13 μM, and BDMC inhibited proliferation in a time- and dose-dependent manner in HepG2 cells. The inhibitory effect was caused by the inactivation of Akt signaling, but not Erk, Jnk or p38 signaling. In addition, the inactivation of Akt signaling was attributed to the inhibition of ubiquitination mediated by K63-Ub but not K48-Ub. Furthermore, we found that BDMC upregulated the expression of CYLD, leading to Akt deubiquitination and inactivation.Conclusion: BDMC inhibited HCC cell proliferation, and that this effect was induced by Akt inactivation via CYLD-mediated deubiquitination.Keywords: bisdemethoxycurcumin, hepatocellular carcinoma, proliferation, deubiquitination